Reduced Virulence of HWP1-Deficient Mutants of Candida albicans and Their Interactions with Host Cells - Tsuchimori, Noboru (American Society for Microbiology, 2000)
The Candida albicans gene HWP1 encodes a surface protein that is required for normal hyphal development in vitro. We used mutants lacking one or both alleles of HWP1 to investigate the role of this gene in virulence. Mice infected intravenously with the homozygous hwp1 null mutant, CAL3, survived a median of >14 days, whereas mice infected with a control strain containing two functional alleles of HWP1 survived only 3.5 days. After 1 day of infection, all strains produced similar levels of infection in the kidneys, spleen, and blood. However, after 2 and 3 days, there was a significant decrease in the number of organisms in the kidneys of the mice infected with CAL3. This finding suggests that the hwp1 homozygous null mutant is normal in its ability to initiate infection but deficient in its capacity to maintain infection. CAL3 also germinated minimally in the kidneys. The ability of the heterozygous null mutant to germinate and cause mortality in mice was intermediate to CAL3, suggesting a gene dosage effect. To investigate potential mechanisms for the diminished virulence of CAL3, we examined its interactions with endothelial cells and neutrophils in vitro. CAL3 caused less endothelial cell injury than the heterozygous hwp1 mutant. We conclude that the HWP1 gene product is important for both in vivo hyphal development and pathogenicity of C. albicans. Also, the ability to form filaments may be critical for candidal virulence by enabling the fungus to induce cellular injury and maintain a deep-seated infection.